The cultural scope and criminological potential of the "hardman story" - Wattis, Louise (Crime, media, culture, 2023)
The true crime genre has become synonymous with the serial killer. As such, other narratives dealing with different types of violent criminal subjects have been overlooked in academic and media analyses. The following article explores a subgenre of true crime which has been overlooked?the life story of the violent criminal or ?hardman biography.? However, in acknowledging the hardman, the discussion also reveals his presence across fact/fiction boundaries and a range of cultural terrain. Following a discussion of the cultural space this figure occupies, I turn my attention to hardman stories which exist predominantly in the local imaginary and focus on one such text which tells the story of a violent protagonist and cultures of crime and violence in the North of England in the late 1980s and early 1990s. In so doing, I focus on how this text animates cultures of violence and marginality left in the wake of deindustrialization and economic decline, combining this with relevant theoretical and ethnographic work. I conclude by arguing that the text is a further example of the way in which popular criminology can complement and advance academic criminological understandings of crime and violence.